Calculation strength of torsion bar suspension of micromirrors (MEOMS) - D. I. Chernyavsky; D. D. Chernyavsky (Омский научный вестник)
The paper considers the strength calculation of the torsion bar suspension of a micromirror with a reflective layer of high optical quality of the surface for deflecting the reflected laser beam. By changing the angle of inclination of the micromirror, the laser beam enters the various input channels of the optical sensor. In this case, a control signal is generated for the further operation of the microcircuit. Thus, the micromirror performs the function of a switch for input optical channels connecting certain input or output elements of the microcircuit in various combinations for further processing. In this work, the calculation of the strength parameters of the mechanical structure of a micromirror made of various materials has been carried out. Practical recommendations related to the development of micromirror torsion bar suspension are given.